Restricting Sales of Menthol Tobacco Products: Lessons Learned from Policy Passage and Implementation in Minneapolis, St. Paul, and Duluth, Minnesota (Mary Ann Liebert, 2021)
Purpose: Commercial tobacco products have historically been target marketed to African American, Latinx, Asian American Pacific Islander, Indigenous, and Lesbian, Gay, Bisexual, Transgender, Queer (LGBTQ) communities, as well as to youth. Menthol cigarettes increase smoking initiation and decrease smoking cessation, particularly among African Americans who smoke menthol cigarettes at higher rates than their white peers. Due to disproportionate tobacco-related health consequences for members of these communities, effective tobacco control policies that restrict availability of menthol products by focusing on retail sales are an important element of addressing health disparities, and require policy efforts informed by leadership and the voice of communities most impacted. This study examines the organizing efforts of three successful policy initiatives in 2017?2018 in Minneapolis, St. Paul, and Duluth, Minnesota, and identifies facilitators and barriers of these campaigns. Methods: We conducted 50 key informant interviews with city council/staff, advocates, and community members and analyzed them for emerging themes. The analysis employed a process-oriented qualitative matrix process to identify emerging themes and divergent perspectives. Results: Following policy implementation, outlets selling commercial menthol tobacco products substantially decreased. Facilitators included strong city council support, leadership from impacted communities, community awareness-building campaigns, and understanding tobacco industry counter-tactics. Challenges included the need to counter tobacco industry misinformation and retailer attempts to circumvent the intent of restrictions. Conclusion: Well-planned advocacy campaigns led by community members most impacted by commercial tobacco can overcome opposition and challenges to restrict sales of menthol tobacco products and successfully reduce availability of these products in their communities.